The promoter of the tgt/sec operon in Escherichia coli is preceded by an upstream activation sequence that contains a high affinity FIS binding site. - Slany, R K (1992)
The tgt/sec operon in E. coli consists of five genes: queA, tgt, ORF12, secD, and secF. QueA and Tgt participate in the biosynthesis of the hypermodified t-RNA nucleoside Queuosine, whereas SecD and SecF are involved in protein secretion. Examination of the promoter region of the operon showed structural similarity to promoter regions of the rrn-operons. An upstream activation sequence (UAS) containing a potential binding site for the factor of inversion stimulation (FIS) was found. Gel retardation assays and DNaseI footprinting indicated, that FIS binds specifically and with high affinity to a site centred at position -58. Binding of FIS caused bending of the DNA, as deduced from circular permutation analysis. Various 5' deletion mutants of the promoter region were constructed and fused to a lacZ reporter gene to determine the influence of the UAS element on the promoter strength. An approximately two-fold activation of the promoter by the UAS element was observed.